2007
DOI: 10.1080/08998280.2007.11928263
|View full text |Cite
|
Sign up to set email alerts
|

Code: Community Diabetes Education for Uninsured Mexican Americans

Abstract: Low-cost diabetes education programs that target Mexican Americans are essential to reduce the observed health disparities in this population. A culturally appropriate intervention was developed as the centerpiece of the Community Diabetes Education (CoDE) program. This article describes the structure, patient acceptance, and costs of this one-to-one educational model delivered in 7 patient contact hours by a community health worker over 12 months in a community clinic serving the uninsured. A total of 162 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…11,12 The CoDE program community health worker had a substantial patient capacity of 120 patients per month, which was not exceeded during the feasibility study period. 17 The patient attrition rate of 22% was consistent with rates observed by other investigators. 15 The results of our feasibility study suggested that patient participation in the CoDE program was influenced by continued patient contact with the community health worker.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…11,12 The CoDE program community health worker had a substantial patient capacity of 120 patients per month, which was not exceeded during the feasibility study period. 17 The patient attrition rate of 22% was consistent with rates observed by other investigators. 15 The results of our feasibility study suggested that patient participation in the CoDE program was influenced by continued patient contact with the community health worker.…”
Section: Discussionsupporting
confidence: 89%
“…Educational and therapeutic guidelines for the three initial educational sessions and the subsequent quarterly educational and assessment components have been described in detail elsewhere. 17 The bilingual community health worker was responsible for delivery of the entire intervention, documentation of all activities within the medical records, and direct, real-time communication with the clinic physicians to address acute medical issues. Health indicators, including a point-of-care HbA1c at baseline and quarterly using a Bayer DCA 20001 Analyzer®, blood pressure measurements with a digital sphygmomanometer, height measurements with a stadiometer, weight measurements with a digital scale, and hand calculations of body mass index (BMI) using the standard formula (kg/m 2 ) were performed by the community health worker during each patient encounter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations